Urban Wage Premia, Cost of Living, and Collective Bargaining - Marianna Belloc; Paolo Naticchioni; Claudia Vittori (Institute of Labor Economics (IZA), 2019)
In this paper, we estimate nominal and real (in temporal and spatial terms) urban wage premia (UWP) in Italy, with its economy characterized by the interplay between collective wage bargaining and spatial heterogeneity in the cost of living. Our dataset for the 2005- 2015 period includes, for workers' characteristics, unique administrative data provided by the Italian Social Security Institute and, for the local CPI computation, housing prices detailed at a fine level of spatial aggregation delivered by the Italian Revenue Agency. For employees covered by collective bargaining, we find a zero UWP in nominal terms and a negative and non-negligible UWP in real terms (-2.6% when all controls are included). To capture the role played by centralized wage settings, we consider various groups of self-employed workers, who are not covered by national labour agreements, while living in the same locations and enjoying the same amenities as employees. We find that, differently from employees, selfemployed workers enjoy a positive UWP in nominal terms, and do not suffer from urban real wage penalties. Results hold under a large array of robustness checks.
Keywords: R12; R31; J31; 330; urban wage premium; cost of living; wage setting